A prospective multicenter study of treosulfan in elderly patients with recurrent ovarian cancer: results of a planned safety analysis - Mahner, Sven (Springer-Verlag, 2012)
BACKGROUND: Treosulfan, an alkylating agent, has demonstrated activity in recurrent ovarian carcinoma. It is equieffective as oral (p.o.) and intravenous (i.v.) formulation. To explore the preference and compliance of elderly patients regarding p.o. or i.v. treosulfan for the treatment of relapsed ovarian carcinoma, women aged 65 years or older were included in this prospective multicenter study. Since elderly patients usually have several concomitant diseases and experience more treatment toxicity, an interim safety analysis was planned and performed after 25 patients finished therapy to assess the tolerability of the treatment regimens. METHODS: Patients had a free choice of treosulfan i.v. (7,000 mg/m(2) day 1 of a 28-day cycle) or p.o. (600 mg/m(2) day 1–28 of a 56-day cycle) for a maximum of 12 cycles (i.v.) or 12 months (p.o.). Indecisive patients were randomized. Toxicity was evaluated according to the NCI-CTC version 2.0. RESULTS: Twenty-five of 51 recruited patients completed therapy at the time of the planned interim analysis (median age, 75 years; range, 70–82). Median ECOG was 1, and median number of prior chemotherapy regimens was 2. A median number of 4 cycles (range, 1–12) were administered per patient. Anemia was the most common hematological toxicity (88 % of patients). Most frequent non-hematological toxicities were nausea (76 %), constipation (68 %), and fatigue (64 %). CONCLUSION: Treatment was generally well tolerated despite the fact that most patients suffered from multiple comorbidities and were heavily pretreated. There were no unexpected hematological or non-hematological toxicities. Based on this safety analysis, the next step of study recruitment was continued.